Metal Complexes of Schiff Bases of 3-Hydroxyquinoxaline-2-carboxaldehyde Encapsulated in Zeolite Y Cages: Potential Catalyst for Removing Phenol from Effluent Media - Suja, N.R.; Bindu Sharmila, T.K.; Amrutha, S.R. (Asian Journal of Chemistry, 2021)
Transition metal complexes are known to be efficient catalyst for many organic transformations. Encapsulation of metal complexes in zeolite cage brings many significant modifications in the structure of the metal complexes, which are very interesting from the catalytic point of view. This study aims in a comparative evaluation of the influence of structure of neat and encapsulated complexes in their catalytic activity. Phenol is one of the major industrial pollutants. Heterogenizing transition metal Schiff bases by encapsulation inside the zeolite would help to minimize the reuse problem of transition metal complexes. This article deals with the synthesis, characterization and catalytic activity studies of Co(II), Ni(II) and Cu(II) complexes of 3-hydroxyquinoxaline-2-carboxaldehyde with ethylenediamine (L1) and an o-phenylene diamine (L2).